The Perioperative Experience of Patients Undergoing Spinal Surgery During the COVID-19 Pandemic: A Qualitative Study - Güven, Betül (Koç Üniversitesi HYO Semahat Arsel Hemşirelik Eğitim ve Araştırma Merkezi (SANERC), 2022)
Background: The novel coronavirus disease (COVID-19) spreading worldwide has caused many restrictions in the lives of individuals as well as in hospitals. There is a need to examine the effects of COVID-19 and these restriction practices on patients undergoing surgical intervention. Methods: The study sample consisted of 20 patients who underwent elective spinal surgery during the COVID-19 pandemic in a training and research hospital in Istanbul. Data were collected via semi-structured interviews by using telephone. The content analysis was used. Results: In this study, the patients stated that they experienced anxiety during the decisionmaking process, were forced to make decision due to the difficulties they experienced, and overcame their concerns by trusting the hospital and their doctors. Most of the patients stated that they had fear of transmission of infection during their hospitalization and expressed that they had trust and distrust of preventive measures taken at the hospital. In addition to patients who felt ready to be discharged after surgery, there were also patients who stated that they wanted to stay in the hospital more due to pain. Most of the patients stated that they tried to cope with the problems such as wound care and pain at home by themselves. Conclusion: The COVID-19 pandemic has had a significant effect on patients who need surgical care. In addition to the implementation of preventive measures against infection, the use of technological applications such as telehealth for educating patients before the surgery and follow-up after surgery can improve the experience of patients in the perioperative process during the pandemic.
Keywords: COVID-19; spinal surgery; qualitative research